PENGEMBANGAN PROSEDUR SISTEM PERKULIAHAN ONLINE YANG EFEKTIF DALAM MENINGKATKAN MINAT BELAJAR MAHASISWA SEKOLAH TINGGI TEOLOGI KRISTUS ALFA OMEGA SEMARANG - Jon, Jon (Shift Key : Jurnal Teologi dan Pelayanan, 2020)
Research on the Development of Online Lecture Systems which is effective in increasing the learning interest of Sekolah Tinggi Teologi Kristus Alfa Omega students aims to describe the Development of the Online Lecture System into a valid, practical and effective product. The method used in this research is Research and Development with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Based on the results of the research that has been done, the Online Lecture System which is effective in increasing student interest in learning is valid for use in Sekolah Tinggi Teologi Kristus Alfa Omega, according to the results of the assessment of two expert teams, namely Waket 1 and Dir. Postgraduate Sekolah Tinggi Teologi Kristus Alfa Omega Semarang with 100 percentages each and the results of student responses were good, namely with a percentage of 81.4% and 81.2%